A magmatic‐hydrothermal origin of the Xinfang gold deposit, Liaodong Peninsula, China, revealed by in‐situ S–Pb isotopes and trace element analyses of pyrite. Issue 2 (7th February 2021) - Yu, Bing; Zeng, Qingdong; Frimmel, Hartwig E.; Zhou, Lingli; Mcclenaghan, Sean H.; Drakou, Foteini; Wang, Yongbin; Chen, Peiwen; Yu, Chuang
Abstract: The Xinfang deposit is a large gold deposit (>20 t of Au) on the southern edge of the Liaodong Peninsula, China. A total of 37 gold‐bearing orebodies are identified along NS‐ and NW‐striking faults and are mainly hosted by the Archean and Neoproterozoic metamorphic rocks. Three stages of hydrothermal mineralization are distinguished, including Stage I of dominant quartz ± pyrite (Py1), Stage II of quartz‐polymetallic sulfide (Py2), and Stage III of quartz‐calcite ± pyrite (Py3). Gold primarily occurs at the Stage II in association with intensive silicification, pyritization, and sericitization. Here, we report on high‐precision in‐situ LA‐MC‐ICP‐MS analyses of S and Pb isotopic compositions of the sulfide minerals and LA‐ICP‐MS analyses of trace element signature of the pyrite from the Xinfang gold deposit. The δ 34 S values of the sulfides range from 1.3 to 5.3‰, which is consistent with a magmatic origin of S. The sulfides yield 208 Pb/ 204 Pb, 207 Pb/ 204 Pb, and 206 Pb/ 204 Pb ratios of 37.497–37.773, 15.323–15.410, and 17.004–17.229, respectively, which deviate from the values of the wall rocks, suggesting an external Pb source. The in‐situ LA‐ICP‐MS spot analyses of the pyrite reveals that gold occurs in two generations of pyrite (Py2 and Py3) but at low concentrations (≤0.06 ppm for Py2, ≤0.24 ppm for Py3). Visible gold, however, only occurs in the Stage II assemblage as inclusions in pyrite and quartz, and is distributed along the margins or within the fractures of the sulfides. The Py2 shows high Co, Ni, and As concentrations and is depleted in other trace elements typical of a magmatic‐hydrothermal derivation. In contrast, Py3 exhibits low concentrations in most trace elements. Trace element mapping of Py2 revealed correlations between Fe and Co, as well as Ni and As, indicating their couped substitution in the pyrite structure. The available geological, petrographic and geochemical data consistently suggest that the Xinfang gold deposit formed during the Early Cretaceous by hydrothermal fluids of magmatic contribution. Abstract : The δ 34 S ratios of sulfides is consistent with a magmatic source of the sulfur. Lead isotope data suggest that the Pb was primarily derived from deep magma instead of the Archean metamorphic rocks. Pyrite chemistry reveal that Stages II and III pyrites are typical of a magmatic‐hydrothermal derivation. The Xinfang gold deposit can be classified as a magmatic‐hydrothermal gold deposit.